Peran Central Education dalam Mendorong Transformasi Desa Wisata Kampung Bawang Merah Purworejo - Erina Agustin; Dwi Ariffatus Sholihah; Cesya Rizkika Parahiyanti (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Purworejo Village is one of the villages in Ngantang Subdistrict that has a lot of potential. One of the prominent potentials is agricultural products, especially shallots. Purworejo village is one of the best suppliers of shallots in Indonesia. This makes many people come to Purworejo Village to conduct research related to shallots. Where this can make Purworejo Village has the potential to become an Educational Tourism Village, but the surrounding community is still unable to utilize it. With the existence of Central Education, it can encourage Purworejo Village to become an Educational Tourism Village. Devotion is carried out in increasing the development of the Purworejo Shallot Village Tourism Village through the role of Central Education. With the Participatory Rural Appraisal (PRA) method through initial observations, conducting forum group discussions with lecturers and resource persons, then conducting educational and mentoring activities, followed by follow-up activities and ending with evaluation actions. This method is applied with the intervention of the Purworejo Village community directly in this service.